First mecC and mecA Positive Livestock-Associated Methicillin Resistant Staphylococcus aureus (mecC MRSA/LA-MRSA) from Dairy Cattle in Malaysia - Aklilu, Erkihun (Microorganisms, 2020)
Livestock associated Methicillin resistant Staphylococcus aureus (S. aureus) (LA-MRSA) was reported to be zoonotic and may transmit to farmers and veterinarians. The objectives of this study were to investigate the occurrence of LA-MRSA from dairy cattle and to evaluate the antimicrobial resistance profiles of the isolates. A total of 63 milk and 32 nasal swab samples were randomly collected from dairy cattle. The samples were processed to isolate S. aureus, MRSA and LA-MRSA using both phenotypic and molecular methods using PCR. The confirmed S. aureus isolates were cultured on oxacillin resistant screening agar base (ORSAB) to detect MRSA and the isolates were further confirmed by PCR targeting the mecA gene. Detection of the novel mecA gene, mecC gene was conducted by PCR amplification. The antimicrobial susceptibility tests were conducted using disc diffusion method. Results revealed 17/95 (17.89%) and 15/95 (15.79%) were positive for mecA and mecC genes respectively. Out of the 15 mecC positive isolates, 12 were positive for both mecA and mecC. The MRSA isolates showed multidrug resistance. The findings showed high prevalence of mecC-positive LA-MRSA in Malaysia and highlight the public health risks to people that may come in contact with the carrier animals or those who may consume unpasteurized milk products from these animals.